WIELE HAŁASU O KARALUCHA (NIEM. SCHWABE I ROS. ПРУСАК, ТАРАКАН) ‒ STUDIUM Z ETYMOLOGII I MOTYWACJI SEMANTYCZNEJ - Stachowski, Marek (Przegląd Rusycystyczny, 2018)
Much ink has been spilled on the sources and history of various names for various species of cockroach. The present author discusses some of them and his main aim is to clear up at least some aspects of what has hitherto been suggested in studies concerning Russian tarakan.